THE EFFECT OF CORPORATE CULTURE AND TALENT MANAGEMENT ON WORK EFFICIENCY AND EMPLOYEE LOYALTY AS AN INTERVENING VARIABLE STUDY OF THE REGIONAL DRINKING WATER COMPANY IN DEMAK REGENCY - Aditya Angger Wibowo (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This study aims to determine how corporate culture and talent management affect work efficiency and employee loyalty at PDAM Kabupaten Demak, intervening or moderating variables. The research objective and study focus is the issue of low work efficiency. Mediation, independent, and dependent are the three variables. Employee loyalty is the intervening variable, talent management and corporate culture are the independent variables, and work efficiency is the dependent variable. This study involved 140 employees, and 105 of them were respondents. Purposive sampling was used. This investigation used SEM-AMOS analysis. The results of this study show that corporate culture does not affect employee loyalty; talent management has a positive and significant effect on employee loyalty; and that corporate culture does not affect work efficiency. Therefore, talent management has a positive and significant effect on work efficiency. Thus, employee loyalty cannot be considered a factor that affects corporate culture and employee loyalty